IMPLEMENTASI NILAI KARAKTER SISWA SD NEGERI 62 PALEMBANG MELALUI PENERAPAN MEDIA PEMBELAJARAN IPS SD BERBASIS EDUTAINMENT - Bunda Harini; Nuraini Usman (Jurnal Inovasi Sekolah Dasar, 2020)
This study aims to describe the implementation of character values for students of SD Negeri 62 Palembang through the application of edutainment-based social studies learning media. This research uses a qualitative approach with descriptive methods. The subjects of this study were second grade students of SD Negeri 62 Palembang. The data collection techniques used in this study were observation and questionnaires and documentation. Edutainment-based learning media used is a game of guessing style. The character values observed when students played the style guess were cooperation, self-confidence, and discipline. Based on the results of observations made, this game is less effective if it is done on grade II students who are included in the low class, because when playing, many students still lack self-confidence. Therefore, it should be applied to high grade students. Keywords: Implementation, Character Value, Edutainment-Based Learning Media